1998
DOI: 10.2105/ajph.88.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of smokeless tobacco use among US youth.

Abstract: OBJECTIVES: The purpose of this study was to provide estimates of the cumulative incidence of initiation of smokeless tobacco use in a cohort of young persons and to explore sociodemographic, environmental, behavioral, and personal predictors of experimentation with and regular use of snuff or chewing tobacco. METHODS: The data for this cohort study were derived from the 1989 Teenage Attitudes and Practices Survey and its 1993 follow-up. The study included 7830 young people 11 through 19 years of age at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 28 publications
(14 reference statements)
3
43
3
Order By: Relevance
“…With respect to age, premalignant lesions were significantly more common in the younger age group (Mean age 32.33±8.76) as compared to oral SCC which was more prevalent in the older age group (53.16±10.14; P<0.05; Table 1). The reason for premalignant lesions being more common in the second and third decades of life may be a function of personal factors, coupled with a weak family structure or support, adult role modeling, peer influences and sports team membership 14 . This was consistent with a study by Hashibe et al 15 who reported increased risk of premalignant lesions in a young population in the United States exposed to the similar tobacco products.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to age, premalignant lesions were significantly more common in the younger age group (Mean age 32.33±8.76) as compared to oral SCC which was more prevalent in the older age group (53.16±10.14; P<0.05; Table 1). The reason for premalignant lesions being more common in the second and third decades of life may be a function of personal factors, coupled with a weak family structure or support, adult role modeling, peer influences and sports team membership 14 . This was consistent with a study by Hashibe et al 15 who reported increased risk of premalignant lesions in a young population in the United States exposed to the similar tobacco products.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in India and Asia have shown parental, sibling, and peer use of tobacco as an influential determinant in continued use (Jeganathan et al, 2013;Odukoya et al, 2013). Tomar and colleagues (1998) provide a caveat beyond this association, finding that smokeless tobacco use by people in the home environment (as well as relatives) were not only marginally predictive of an "experimentation" level of SLT use, but were also significantly predictive of continued use (Tomar et al, 1998). For this reason, we can infer that this finding may be based on a survey design limitation.…”
Section: 6553 Analysis Of the Motivating Factors For Smokeless Tobacmentioning
confidence: 99%
“…Many young people start using tobacco even as early as the age of 11Á14 (Tomar & Giovini, 1998;Rolandsson & Hugoson, 2000). Over a third of all children in ninth grade in the Swedish school system use tobacco regularly, some even on a daily basis (CAN, 2004).…”
Section: Introductionmentioning
confidence: 99%